Time to presenting to hospital and associated factors in stroke patients (Swiss Medical Weekly, 2011)
OBJECTIVE:To investigate multifaceted factors that constrain early stroke treatment, from both clinical and social standpoints. METHODS: This was a cross-sectional study conducted at a general hospital in northern Japan. Data on time to presenting to hospital after stroke onset and its potential associated factors were retrospectively extracted from the medical records of hospitalised stroke patients and analysed. RESULTS:Median time of presenting to hospital after stroke onset for 287 patients was 12 hours (range, 0.4–347 hours), and 16.7% of cases presented within 2 hours of onset. Multivariate analysis revealed a significant level of association between a Japan Coma Scale score of ≥1 (OR = 0.41; 95% CI, 0.20–0.86) and cardiogenic cerebral embolism (OR = 0.36; 95% CI, 0.15–0.85). The proportions of patients treated with recombinant tissue plasminogen activator, those with a Modified Rankin Scale score of ≥2, and those in a rehabilitation hospital/long-term care ward or who died were significantly higher among patients who presented within 2 hours. CONCLUSION: Less than one fifth of our stroke patients presented to hospital within 2 hours. Although our results are preliminary given their limited generalisability and the retrospective nature of data collection, medical rather than social factors were found to be associated with time of presenting to hospital. Patients with severe symptoms presented to the hospital at an earlier stage after stroke onset. It is important to promote the earliest possible presentation to hospital after a stroke.